Formulation and Evaluation of Novel Mouth Dissolving Film of Tofacitinib Citrate by Using 3\(^2\) Full Factorial Design - Meghana Raykar; Malarkodi Velraj (Advanced Concepts in Pharmaceutical Research Vol. 1, 2023)
Objective: The aim of the present study was to design and evaluation of mouth dissolving oral films of tofacitinib citrate allowing fast reproducible drug dissolution in oral cavity thus bypassing the first-pass metabolism to enhance the patient convenience. Method: Films has been prepared by solvent casting technique by using Polymer and Plasticizers. Results: The results of prepared film pH, Thickness, Folding Endurance, Disintegration time, drug content was found in the suitable range. Conclusion: The present study shown that the MDFs of Tofacitinib could be successfully prepared by solvent casting technique. Further, it was concluded that formulation F3 and F6 containing 45% w/w and 50% w/w of polymer concentration respectively were found to be having satisfactory physicochemical and mechanical properties. Also, the stability study of these two optimized formulations confirmed the longer shelf life of MDFs.